(untitled) (Bangladesh Journal of Agricultural Research, 2010)
A polymerase chain reaction (PCR) based approach, namely random amplified polymorphic DNA (RAPD) analysis was applied to l0 varieties of onion (Allium cepa) in order to assess the degree of polymorphism within the genes and to investigate if this approach was suitable for genetic studies of onion. For this study, ten cultivars of onion were evaluated for variability using a set of 15 random l0-mer primers. The polymorphisms in PCR amplification products were subjected to the unweighed pair group method for arithmetic averages (UPGMA) and plotted in a phenogram. The dendogram constructed from the similarity data showed that all the cultivars analyzed were related. Among them, 12 of the primers revealed scorable (168 bands) polymorphisms between cultivars of A. cepa and the rest did not show polymorphism in their genetic level. In this study, it was found that Bermis and India-2 were more dissimilar and on the other hand, Faridpuri and Bhati were the most similar in their genetic level. Keywords: RAPD; onion; genetic diversity; polymorphism. DOI: 10.3329/bjar.v35i2.5894 Bangladesh J. Agril. Res. 35(2) : 313-322, June 2010